PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DALAM PEMBELAJARAN PECAHAN DI KELAS IV SDN 12 BANAWA SELATAN - Rahayu, Sri; Kertayasa, I Ketut; Anta, I Made Nuhari (JATMIKA : Journal Education and Learning of Elementary School, 2024)
'This study aims to determine the learning outcomes and student activities in learning fractions in class IV SD by applying the Two Stay Two Stray model. The research model is classroom action research with two cycles which have stages of planning, implementing, observing and reflecting. The results of students pretest classical absorption in cycle I was 64.7% and the posttest was 69.2%. While the results of students pretest classical absorption in cycle II were 71.6% and posttest were 79%. The percentage increase in the results of the classical pretest absorption was 4.5% while the increase in the posttest classical absorption was 7.4%. The percentage of observation results of teacher activities in cycle 1 was 76%, and the percentage of observation results of student activities was 77%, while in cycle II the percentage of teacher activity results was 78% and the results of observation of student activities was 78%. Increasing the percentage of observations of teacher activities by 5% and increasing the percentage of observations of student activities by 10%. Based on this analysis, learning using the two stay two stray model on fractional material is declared successful.